Perturbations of an Ostrowski type inequality and applications - Nenad Ujević (International Journal of Mathematics and Mathematical Sciences)
Two perturbations of an Ostrowski type inequality are established. New error bounds for the mid-point, trapezoid, and Simpson quadrature rules are derived. These error bounds can be much better than some recently obtained bounds. Applications in numerical integration are also given.